From sherds to landscapes (Chicago, Illinois)
xxiv, 337 sayfa
Keywords: “This volume honors McGuire Gibson and his years of service to archaeology of Mesopotamia, Yemen, and neighboring regions. Professor Gibson spent most of his career at the University of Chicago's Near Eastern Languages and Civilizations department and the Oriental Institute. Many of his students, colleagues, and friends have contributed to this volume, reflecting Gibson's diverse interests. The volume presents new results in areas such as landscape archaeology, urbanism, the ancient languages of Mesopotamia, history of Mesopotamia, the archaeology of Iran and Yemen, prehistory, material culture, and wider archaeological topics“ --